SYNTHESIS OF IRON OXIDE USING FEBDC TEMPLATES AS ACTIVE MATERIALS FOR NONENZIMATIC ELECTROCHEMICAL SENSORS FOR GLUCOSE DETECTION - Abdurrahman Abrori, Syauqi
Early detection is one important step in preventing the spread of disease. Electrochemical sensors offer a method for detecting diseases that is simpler, faster, and more accurate than conventional laboratory analysis methods. In this research, a material for non-enzymatic glucose sensor will be made because it has various advantages including high stability because it does not depend on enzymes, high sensitivity and low cost. Currently, the material that has been developed as an electrochemical sensor is the Metal-Organic Framework (MOF). MOF is a hybrid material with a metal core coordinated with organic ligands. One of the MOF that began to be developed is FeBDC. FeBDC is MOF with ferrous metal (Fe) being the core and binding to organic terephthalic acid (H2BDC) ligands and N, N-dimethylformamide (DMF). FeBDC synthesis was carried out using the solvothermal method. This method was chosen because it can produce MOF with a high surface area, a fairly easy working process, and low production costs. FeBDC has been successfully synthesized using the solvothermal method. FeCl2.4H2O and Benzene-1,4-dicarboxylic acid (H2BDC) are used as precursors to form FeBDC particles. The resulting MOF yields good crystallinity and morphology according to the references. Electrochemical properties were tested using cyclic voltammetry (CV) with a 0.1M ph 7.4 PBS solution as the supporting electrolyte. The measurement results show the reduction and oxidation curve cycle of FeBDC and show that the material can be a good electron transfer medium between the electrode surface and the electrolyte solution. This can be seen from the increasing peak of oxidation and reduction currents. The FeBDC sample obtained has a sensitivity of 0.4 µA.mM-1.cm-2, a linear range between 3 to 9 mM, and a glucose detection limit of 44 µM. Keywords: Fe-MOF-74, Fe3O4, glucose, electrochemical, non-enzymatic